2019
DOI: 10.1051/epjconf/201920501004
|View full text |Cite
|
Sign up to set email alerts
|

Multi-mJ mid-IR light bullets in air

Abstract: We examine mid-IR light bullets generated in ambient air. 2-optical cycle pulses confined in space are generated in filamentation regime. Few-fold solitonic self-compression is achieved for strongly chirped mid-IR pulses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…They demonstrated that stable bullets had bell-shaped solitons, whereas unstable bullets were transformed into the shape of rockets. Furthermore, the formation of light bullets upon ultrashort laser pulse filamentation in dissipative media such as air, fused silica, fluorite, etc., has been studied in the presence of different physical effects, see [34][35][36][37][38]. For more examples of investigating the propagation characteristics of optical bullets, the reader is referred to the following studies [39][40][41][42][43][44][45][46][47].…”
Section: Introductionmentioning
confidence: 99%
“…They demonstrated that stable bullets had bell-shaped solitons, whereas unstable bullets were transformed into the shape of rockets. Furthermore, the formation of light bullets upon ultrashort laser pulse filamentation in dissipative media such as air, fused silica, fluorite, etc., has been studied in the presence of different physical effects, see [34][35][36][37][38]. For more examples of investigating the propagation characteristics of optical bullets, the reader is referred to the following studies [39][40][41][42][43][44][45][46][47].…”
Section: Introductionmentioning
confidence: 99%